MiR-126 suppresses neuronal apoptosis in rats after cardiopulmonary resuscitation via regulating p38MAPK. (April 2020) - Pan, H; Yu, M; Chen, M; Wang, X; Zhang, H; Du, S; Yu, S
In this study, we aimed to evaluate the effect of microRNA-126 (miR-126) on neuronal apoptosis in cardiopulmonary resuscitation rats and to explore the related molecular mechanism. The expression of miR-126 in brain tissues of rats after cardiopulmonary resuscitation was measured by real-time fluorescence quantitative polymerase chain reaction (RT-qPCR). The basic parameters of cardiopulmonary resuscitation were recorded by miR-126 mimic injection in rats after cardiopulmonary resuscitation. Hematoxylin–eosin staining was used to observe the pathological changes of hippocampus. Immunohistochemistry was used to observe the expression of p38 and caspase-3 protein. Furthermore, the expression of p38 mitogen-activated protein kinase (p38MAPK), Jun N -terminal kinase (JNK), and extracellular signal-regulated kinase 1/2 (ERK1/2) in rat hippocampus was detected by RT-qPCR and Western blot. In order to confirm whether miR-126 takes part in the p38MAPK pathway in the hippocampus of rats after cardiopulmonary resuscitation, the p38MAPK pathway inhibitor (SB203580) and activator (anisomycin) were added. The results showed overexpression of miR-126 could significantly increase the neurological function score and improve the pathological morphology of hippocampus in rats after cardiopulmonary resuscitation. miR-126 overexpression also could reduce the neuronal apoptosis, p38, and caspase-3 expression in the hippocampus. Moreover, the p38MAPK and JNK expression was downregulated and ERK1/2 expression was upregulated after miR-126 mimic injection ( p < 0.05). The results of inhibition of p38MAPK pathway were consistent with those of overexpression of miR-126 ( p > 0.05). This study indicated miR-126 could significantly reduce neuronal apoptosis of hippocampus in rats after cardiopulmonary resuscitation, which might be involved in the regulation of p38MAPK pathway.